Analysis Towards the Factors Relates to the Yield at Sharia Bond Which Listed on Indonesia Stock Exchange During Period of 2020 - Feriatna, Troynanda; Marsoem, Bambang Santoso (Dinasti International Journal of Economics, Finance & Accounting, 2022)
This research analyzes the influence caused by the debt equity ratio (DER), maturity, firm size and rating of Islamic bonds on the yield to maturity (YTM) from corporate Islamic bonds. The research population consisted of corporate sharia bonds traded at the Indonesia Stock Exchange during period of 2020. The sample choosen technique was performed by purposive sampling. The research sample consisted of 59 corporate bonds that issued from 13 companies through all sectors except the banking and financial sectors. The research analysis method used descriptive statistics and multiple linear regression. The outcomes showed partially that the maturity variable had a significant positive affect to YTM, Rating had a negative affect on YTM, while DER and Islamic bond ratings had no affect on YTM. The research implication stated that companies need to increase their sharia bond ratings in order to maintain investor trust. For further research, it is expected to analyze other variables which had an impact to YTM because the coefficient of determination that reached from this research are 67%, while the remaining of 33% was determined by other variables which not explained in this research.